Gemcitabine–carboplatin–paclitaxel combination as first-line therapy in advanced ovarian carcinoma: a single institution phase II study in 24 patients. (1st January 2006) - Fuso, L.; Amant, F.; Neven, P.; Berteloot, P.; Vergote, I.
Abstract : Single-agent gemcitabine demonstrated response rates of 11–60% in platinum/paclitaxel-resistant ovarian cancer. Twenty-four patients with epithelial ovarian cancer were treated with gemcitabine 800 mg/m 2 on days 1 and 8, carboplatin area under the curve 5 on day 1, and paclitaxel 175 mg/m 2 over 3 h on day 1 every 3 weeks for six cycles. Median age was 54 years, and FIGO stage distribution was IIC, 1 patient, III, 18, and IV, 5. A total of 22 (92%) patients completed all the six planned courses of chemotherapy. Doses were reduced in 8 out of 24 (33%) patients. Of the 17 patients with measurable disease, 15 underwent an interval debulking surgery. Prior to interval debulking surgery, all 15 patients had a partial response according to the response evaluation criteria in solid tumors criteria. Overall in the 17 patients with measurable disease, the response rate at the end of the first-line chemotherapy (including interval debulking) was 94% (14 [82%] complete response and 2 [12%], partial response). One patient (6%) received only one cycle due to early progression. Using the CA125 criteria as defined by the Gynecologic Cancer Intergroup, all patients had at least a partial response prior to interval debulking, and the overall response rate of the whole first-line chemotherapy and interval debulking ( n = 15) was observed in 21 out of 23 patients (91%). The dose-limiting toxicity was bone marrow toxicity. Median overall survival was 28 months, and the 2-year actuarial survival was 73%. The gemcitabine, carboplatin, paclitaxel triplet has an acceptable toxicity with high response rates as first-line therapy in advanced ovarian cancer.